SiC Based Power Converter for Industrial Induction Hardening of Steel Probes - Mendi Altube, Amaiur; Villar Iturbe, Irma; Carretero Chamarro, Claudio; Acero Acero, Jesus (Jornada de Jóvenes Investigadores del I3A, 2022)
This article describes the design and start-up of a SiC-based power converter topology for induction heating applications. This converter is conceived as a versatile tool for further research activities on the new heating processes currently demanded by the metal industry.